2018
DOI: 10.24926/iip.v9i2.989
|View full text |Cite
|
Sign up to set email alerts
|

Using the Plan-Do-Study-Act (PDSA) Model for Continuous Quality Improvement of an Established Simulated Patient Program

Abstract: Objective: To describe the use of a continuous quality improvement process for strengthening our simulated patient (SP) program and the initial steps that have been implemented.  Innovation: A workgroup that included five clinical faculty with significant experience working with SPs and a strong interest in improving the SP program was developed.  The Plan-Do-Study-Act model was used as it allowed for incremental quality improvement changes, in order to ensure a high-quality SP program designed to optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This group used the Plan-Do-Study-Act (PDSA) model to conduct an initial evaluation of the program and subsequently identified that the clinical faculty alone did not have the capacity to carry forth comprehensive CQI efforts vital to further develop the SP program. 5 With administrative leadership support, the College created a staff position focused on SP program development, administration, and evaluation. While creating and sustaining a culture of assessment is a team effort and requires buy-in from all stakeholders, finding a person dedicated to upholding the principles of CQI has helped our SP program maintain its commitment to assessment.…”
Section: Leadershipmentioning
confidence: 99%
See 2 more Smart Citations
“…This group used the Plan-Do-Study-Act (PDSA) model to conduct an initial evaluation of the program and subsequently identified that the clinical faculty alone did not have the capacity to carry forth comprehensive CQI efforts vital to further develop the SP program. 5 With administrative leadership support, the College created a staff position focused on SP program development, administration, and evaluation. While creating and sustaining a culture of assessment is a team effort and requires buy-in from all stakeholders, finding a person dedicated to upholding the principles of CQI has helped our SP program maintain its commitment to assessment.…”
Section: Leadershipmentioning
confidence: 99%
“…This group used the Plan-Do-Study- Act (PDSA) model to conduct an initial evaluation of the program and subsequently identified that the clinical faculty alone did not have the capacity to carry forth comprehensive CQI efforts vital to further develop the SP program. 5 …”
Section: Utilization Of the Assessment Culture Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Because this was a QI initiative, this was exempted from the necessity of ethical board approval. Because of the nature of this quality design, this will be written as a plan, do, study, act format (Fishman et al, 2013;Barker et al, 2018;AHRQ, 2018;IHI, 2019;Vordenberg et al, 2018).…”
Section: Activity Designmentioning
confidence: 99%
“…However, the methodical integration of improvement cycles such as PDSA are often lacking in practice, largely due to the high resource requirements of frequent programmatic assessments and data review [ 10 ]. Despite the broad application of PDSA cycles in quality improvement paradigms, and the emphasis on CQI in curriculum development, there remains a paucity of data regarding the usefulness of applying the PDSA cycle to improve medical education sessions [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%